Pembatasan Hak Ekslusif terhadap Penggunaan Kata Umum dalam Sebuah Merek - Sanjaya, Aqila Herdiyanto; Silalahi, Wilma (Universitas Muhammadiyah Ponorogo, 2025)
Technological advances drive the importance of brands as trade identities. Based on Law No. 20 of 2016, brands with generic words are prohibited, but the lack of clarity in the rules creates legal uncertainty. This study examines the legal issue and evaluates the regulations to support fair trademark law in Indonesia. This study applies a normative legal approach method with analytical descriptive research specifications. This approach aims to explain and describe the events that are the focus of the study, which are then analyzed by referring to primary, secondary, and tertiary legal materials. The results of this study are the Restriction of exclusive rights to generic words in brands, as regulated in Article 16 letter f of the Permenkumham Merek 12/2021, preventing monopoly of widely known terms to protect the public interest and support business competition. However, the lack of a clear classification in Law No. 20 of 2016 creates the potential for legal conflicts. Distinctive power remains a key element, which can be obtained through fantasy words, generic words unrelated to the product, or secondary meanings. Clearer guidelines and evaluation of the mechanism of distinctive power are needed for fair and effective application of the law.